2022
DOI: 10.1021/acsmaterialsau.2c00006
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Synthesis of Xylan Microparticles with Tunable Morphologies

Abstract: Xylans are a diverse family of hemicellulosic polysaccharides found in abundance within the cell walls of nearly all flowering plants. Unfortunately, naturally occurring xylans are highly heterogeneous, limiting studies of their synthesis and structure–function relationships. Here, we demonstrate that xylan synthase 1 from the charophyte alga Klebsormidium flaccidum is a powerful biocatalytic tool for the bottom-up synthesis of pure β-1,4 xylan polymers that self-assemble into microparticles in vitro. Using ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In diseased ginseng, we found that one cellulose synthase (UDP-forming) gene was upregulated, and two EG genes were differential expression ( Figure 8 ). Xylans are a diverse family of hemicellulosic polysaccharides found in abundance within the cell walls of nearly all flowering plants ( Smith et al., 2022 ). Two transcripts of xylan synthase had inhibited expression in the rusty ginseng root ( Figure 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…In diseased ginseng, we found that one cellulose synthase (UDP-forming) gene was upregulated, and two EG genes were differential expression ( Figure 8 ). Xylans are a diverse family of hemicellulosic polysaccharides found in abundance within the cell walls of nearly all flowering plants ( Smith et al., 2022 ). Two transcripts of xylan synthase had inhibited expression in the rusty ginseng root ( Figure 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Xylose is, in most cases, the monosaccharide monomer that is found in the highest quantity, although in softwoods, mannose can be the most abundant monosaccharide. It is worth mentioning that acidified forms of regular monosaccharides can be found in hemicellulose, including glucuronic acid and galacturonic acid [68].…”
Section: Cellulose and Hemicellulosementioning
confidence: 99%